2020
DOI: 10.1177/0042098020902739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green space on walking: Does size, shape and density matter?

Abstract: The role of the built environment in improving public health through fostering physical activity has come under increased scrutiny in recent years. This study investigates relationships between walking activity and the configuration of green spaces in Greater London. Pedestrian activity for N = 54,910 walking trip stages is gathered through the London Travel Demand Survey (LTDS), with routes between origin and destination mapped onto the street network from the Integrated Transport Network of Ordnance Survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 35 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…At the same time, personalized protection in parks, public spaces and while biking is necessary to reduce the risks of clusters developing when outside crowding replaces inside crowding [ 14 ]. The size of public green spaces in cities clearly influences this risk [ 15 ]. Planning standards for green space, which typically focus on pro rata provision (square meters pp) may need to be revisited to emphasis accessibility to large spaces.…”
Section: Commentarymentioning
confidence: 99%
“…At the same time, personalized protection in parks, public spaces and while biking is necessary to reduce the risks of clusters developing when outside crowding replaces inside crowding [ 14 ]. The size of public green spaces in cities clearly influences this risk [ 15 ]. Planning standards for green space, which typically focus on pro rata provision (square meters pp) may need to be revisited to emphasis accessibility to large spaces.…”
Section: Commentarymentioning
confidence: 99%
“…Consistent with the main ES uses presented in this study, Kaczynski, Potwarka and Saelens [43] also reported from Ontario, Canada and Campbell, Svendsen, Sonti and Johnson [30] from New York City, NY, USA, physical activities to be the predominant park use, but contrastingly mainly influenced by park facilities enabling the intended use, while the factor distance or proximity played a minor role for users in Ontario, but not in New York City. Furthermore, Zhang et al [81] reported proximity to retail areas having a positive effect on park visits for walking in a study in Greater London.…”
Section: Urban Es Uses and Factors Influencing Themmentioning
confidence: 99%
“…The provision of green infrastructure can also encourage active lifestyles amongst the wider population [40]. Green corridors with integrated active transport networks reinforce walking and cycling in cities [41,42]. Active lifestyles reduce obesity, levels of stress and improve the mental health of city dwellers, helping to build long-term health resilience [43][44][45].…”
Section: Health Benefitsmentioning
confidence: 99%